Modulation of erythropoietin formation by changes in blood volume in conscious dogs. - Ehmke, Heimo; Just, Armin; Eckardt, K. U.; Persson, Pontus B.; Bauer, C.; Kirchheim, Hartmut (The journal of physiology, 1995)
1. A possible influence of the filling of the circulatory system on the plasma concentration of erythropoietin, which is the major regulator of erythrocyte formation, was investigated in conscious dogs. 2. Over an experimental period of 5 h, the animals were subjected to either haemorrhage (hypovolaemia), blood volume expansion (hypervolaemia), or exchange transfusion of blood with dextran (isovolaemic anaemia). 3. A reduction of blood volume by 20% induced by haemorrhage increased plasma erythropoietin levels approximately 1.5-fold in the absence of significant changes in haematocrit. 4. An expansion of blood volume by 12% induced by an intravenous infusion of dextran did not change plasma erythropoietin levels, although the haematocrit decreased by 0.04. 5. A reduction of the haematocrit by 0.12 in the absence of changes in blood volume induced by an isovolaemic exchange transfusion (dextran vs. blood) increased plasma erythropoietin levels approximately 3-fold. 6. Total renal oxygen supply did not change in any of the three experimental protocols. 7. These data indicate that in dogs the erythropoietin production rate is modulated by changes in blood volume, and suggest a possible role of erythropoietin in the regulation of blood volume.
Gesehen am 25.11.2024